Lipoid proteinosis - Mukhija Pooja; Singh Shweta; Singh Shailendra; Mukhija R (Wolters Kluwer Medknow Publications, 2006)
A three and half years old female child with lipoid proteinosis with no history of parental consanguinity and affected siblings has been reported here. The patient presented with complant of delayed healing, persistent oozing lesions which is quiet unusual as compared to that of hoarseness of voice which is usually the presenting complaint.